Estimación de parámetros químicos y biológicos en oxisoles con uso citrícola Estimation of chemical and biological parameters on oxisols with Citrus - Humberto C Dalurzo (Ciencia del Suelo, 2005)
El objetivo de este estudio fue estimar el efecto del sistema de producción citrícola sobre algunas propiedades químicas y biológicas del suelo, a fin de obtener indicadores de calidad. Se estableció un ensayo con 2 tratamientos: selva subtropical (Sv) y uso citrícola (Ci. El diseño fue en bloques completamente aleatorizados. Se tomaron muestras compuestas de 0-10 cm de profundidad. Se determinaron: pH, carbono orgánico (CO), materia orgánica particulada (MOP), fósforo asimilable (P), nitrógeno total (Nt), nitrógeno potencialmente mineralizable (NPM), actividad de la fosfatasa ácida (APA), y respiración del suelo (RES) como variables de respuesta. El contenido promedio de CO fue mayor en la Sv (4,03 %) respecto al Ci (2,35%). A pesar del aporte de N al Citrus, el Nt y el Npm fueron mayores en la Sv. En la MOP y sus fracciones, se hallaron diferencias significativas presentando la Sv los mayores valores. El Nt explicó el 69% de la variancia de la APA y el CO el 61%: APA = 1.775 N 153,7 (r² = 0,.69). APA = 221 CO - 230 (r² = 0.61). La disminución producida por el uso citrícola revelaría que los atributos: CO, Nt, APA, NPM, MOP y RES, serían indicadores sensibles de la calidad del suelo. Knowledge about the impact of agricultural practices on soil quality is very important to plan the use and sustainable management of productive lands. Citrus cropping has recently acquired a significant economic importance in Misiones, Argentina. It is cultivated in different types of soils sensitive to erosion, like Oxisoles. The aim of this work was to determine the effect of citrus cropping on some chemical and biological soil quality indicators. The field experiment consisted of 2 treatments: subtropical rainforest (Sv) and citrus (Ci). In 0-10 cm samples the following parameters were measured: pH, organic carbon (OC), particulate organic matter (POM), total nitrogen (TN), available phosphorus (P), acid phosphatase activity (APA), respiration (RES), and potentially mineralizable nitrogen (PMN). The comparisons of the mean treatments were carried out through Duncan´s Multiple Range Test (P < 0.05). The average OC content was higher in Sv (4.03 %) than in Ci (2.35). In spite of N addition to Citrus, TN and PMN were higher in Sv than in Ci. Sv showed the highest values (statistically different from Ci) in POM and its fractions. Nt accounted for 69% of the APA variance and the OC a 61%: APA = 1.775 TN 153.7 (r2 = 0.69). APA = 221 CO - 230 (r2 = 0.61). Obtained results showed that citrus cultivation decreases OC, TN, APA, PMN, POM and soil respiration, which accelerated soil degradation. These soil attributes should be considered as indicators to assess soil quality.